Galunisertib suppresses the staminal phenotype in hepatocellular carcinoma by modulating CD44 expression - Rani, Bhavna (Cell Death Dis, 2018)
Cancer stem cells (CSCs) niche in the tumor microenvironment is responsible for cancer recurrence and therapy failure. To better understand its molecular and biological involvement in hepatocellular carcinoma (HCC) progression, one can design more effective therapies and tailored then to individual patients. While sorafenib is currently the only approved drug for first-line treatment of advanced stage HCC, its role in modulating the CSC niche is estimated to be small. By contrast, transforming growth factor (TGF)-β pathway seems to influence the CSC and thus may impact hallmarks of HCC, such as liver fibrosis, cirrhosis, and tumor progression. Therefore, blocking this pathway may offer an appealing and druggable target. In our study, we have used galunisertib (LY2157299), a selective ATP-mimetic inhibitor of TGF-β receptor I (TGFβI/ALK5) activation, currently under clinical investigation in HCC patients. Because the drug resistance is mainly mediated by CSCs, we tested the effects of galunisertib on stemness phenotype in HCC cells to determine whether TGF-β signaling modulates CSC niche and drug resistance. Galunisertib modulated the expression of stemness-related genes only in the invasive (HLE and HLF) HCC cells inducing a decreased expression of CD44 and THY1. Furthermore, galunisertib also reduced the stemness-related functions of invasive HCC cells decreasing the formation of colonies, liver spheroids and invasive growth ability. Interestingly, CD44 loss of function mimicked the galunisertib effects on HCC stemness-related functions. Galunisertib treatment also reduced the expression of stemness-related genes in ex vivo human HCC specimens. Our observations are the first evidence that galunisertib effectiveness overcomes stemness-derived aggressiveness via decreased expression CD44 and THY1.